The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1101/2020.06.25.171611
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generation of Heart Organoids Modeling Early Human Cardiac Development Under Defined Conditions

Abstract: Cardiovascular-related disorders are a significant worldwide health problem. Cardiovascular disease (CVD) is the leading cause of death in developed countries, making up a third of the mortality rate in the US 1 . Congenital heart defects (CHD) affect ~1% of all live births 2 , making it the most common birth defect in humans. Current technologies provide some insight into how these disorders originate but are limited in their ability to provide a complete overview of disease pathogenesis and progression due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…Reflections on intestinal organoids have centered on their use in CF-related work (e.g., precision medicine, biobanking). Nonetheless, multiple other human organoid systems have been reported (Israeli et al, 2020;Kim et al, 2020). Consequently, broader inquiry is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Reflections on intestinal organoids have centered on their use in CF-related work (e.g., precision medicine, biobanking). Nonetheless, multiple other human organoid systems have been reported (Israeli et al, 2020;Kim et al, 2020). Consequently, broader inquiry is needed.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Wnt and BMP signaling pathways were identified as critical cues for cardiac organoid selforganization and chamber formation in 3D, in which CMs and endothelial cells were both formed in the same aggregates. 19,20 With the advent of optogenetic control of BMP signaling, 23 we may be able to precisely pattern the differentiation of CMs, endothelial cells and/or epicardial cells via optogenetics to achieve spatially-organized cardiac tissues/ organoids with high consistency and reproducibility. In the future, OptoWnt could be combined with 3D cell culture, orthogonal light control of other developmental signaling pathways, and advanced optical patterning techniques to achieve more physiologically relevant hPSC organoid models with intricate geometries and orthogonally controlled cell positions for studying human development and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry analysis demonstrated that $80% of the day 15 cells were cTnT + CMs, with a differentiation efficiency ($82.7% 17 ) comparable to our previous GiWi protocol. 15 19,20 we illuminated day 6 cardiac progenitor aggregates for 24 hours, leading to self-organized cardiac organoids with a cavity (Figure S3B). Our results highlight the potential of our OptoWnt platform for light-controllable tissue patterning in hPSCs.…”
Section: Light-induced Cardiac Differentiation In Hpscsmentioning
confidence: 99%
“…Protocols to derive 3D heart models have been tested since at least 2007, and, to date, there is a great variation of possibilities. [91] The most recent publications indicate generation of heart organoids that present different cell types such as myocytes, epicardial cells, endocardial cells, endothelial cells, and fibroblasts, [91] including models in which biological and physiological pacemakers are derived within the culture. [92] The applications include infarct modeling, drug screening, cell therapy, understanding of heart development, and even determination of function of each cardiac cell type.…”
Section: Heartmentioning
confidence: 99%